Forrageamento de abelhas sem ferrão Melipona subnitida (Apidae, Meliponini) em uma área de brejo de altitude no nordeste brasileiro - Sá Filho, Geovan Figueirêdo de (Universidade Federal Rural do Semi-Árido, 2016)
The climatic characteristics of the Brazilian Tropical Dry-Forest, the Caatinga in northeastern Brazil, directly influence the activities of bees occurring in this region. Due to future climate warming, some species may change their geographic distribution towards "climate refuge habitats" particularly at higher altitudes. In this study, we investigated the foraging activity of Melipona subnitida (Apidae, Meliponini), a stingless bee species highly adapted to the hot and semiarid climate of the Caatinga. We investigated, whether this bee adjusts its foraging activity to the climatic conditions of the Moist Forest Enclaves at high altitudes located within the Caatinga biome, characterized by lower ambient temperatures and higher rainfall compared to the surrounding lowland regions. For this, we studied the pollen and nectar foraging activity of four colonies of M. subnitida at Martins-RN, which is situated at an altitude of approximately 750 m. Between March and December of 2015, we counted the number of foragers during 5 minutes every half hour (between 05:00-08:00) and hourly (between 09:00-17:30) and registered the ambient temperature. The thermal window of pollen foraging (range of environmental temperatures at which 90% of bees returned to the colony) was between 20 and 31 ° C (range = 11 ° C) and that of nectar foraging between 20 and 31 ° C (range = 11 ° C). The difference between pollen and nectar foraging concerning the thermal window was statistically significant (TMED-Pollen = 23 ° C; TMED-Nectar = 25 ° C; Mann-Whitney Rank-Sum-Test: P <0.001). Our results indicate that M. subnitida is able to adjust its foraging activity to the climatic conditions prevailing at Moist Forest Enclaves, mainly through adjusting its lower temperature threshold to the low ambient temperatures in the morning in this habitat, which are significantly lower than those of lowland Caatinga regions. These results indicate that Moist Forest Enclaves at high altitudes are possible refuge habitats for M. subnitida in view of global warming predicted for the coming decades
Keywords: Abelha jandaíra; Caatinga; Coleta de recursos; Bee jandaíra; Caatinga; Resource collection; CIENCIAS BIOLOGICAS::ECOLOGIA